ANALYSIS OF LIBERAL FEMINISM IN THE NOVEL MULAN'S SECRET PLAN BY TESSA ROEHL - Lolita Dewi Ni Kadek (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
The aims of this study are to identify the liberal feminism that found in the novel Mulan’s Secret Plan by Tessa Roehl. In liberal feminism women should have a same right and same opportunity as a man. The liberal feminism could be seen in the character of Mulan in the novel Mulan’s Secret Plan. Mulan struggled for her right to get educational opportunities same as man and struggle for her right to freely choose what she wants to do. In order to understand how the aspect of liberal feminism were found in the novel, the theory of liberal feminism proposed by (Tong, 2008) were utilized in this study. This study used observation method to collect the data and qualitative method to analyze data. The result of this study indicates the aspect of liberal feminism in Mulan character were equal education and equal liberty.